Development of a Storytelling Module to Reduce Hospitalization Anxiety in Preschool Children: A Pediatric Nursing Intervention - Suraya, Citra; Wisuda, Aris Citra; Sansuwito, Tukimin bin; Dioso, Regidor III (International Journal Scientific and Professional, 2025)
Hospitalization is often a stressful experience for preschool children, frequently leading to elevated anxiety due to separation from caregivers, unfamiliar medical environments, and invasive procedures. Storytelling, as a developmentally appropriate and therapeutic communication method, offers a promising approach for pediatric nurses to reduce emotional distress in young patients. This study aimed to develop a storytelling module as a pediatric nursing intervention to reduce hospitalization anxiety in preschool-aged children. A Research and Development (R&D) approach was employed using the Borg and Gall model. The study was conducted from April to June 2024 at Siti Khadijah Islamic Hospital, Palembang. The development process involved a literature review, expert validation by pediatric nurses, child psychologists, and linguists, module drafting, and limited field testing. The participants included 20 hospitalized children aged 3–6 years and five pediatric nurses. Anxiety levels were measured using the State-Trait Anxiety Inventory for Children (STAI-C) before and after the intervention, with descriptive analysis used to assess outcomes. The finalized module comprised six storytelling themes, colorful visual aids, and structured nursing guidelines designed to address common sources of hospitalization anxiety in preschoolers. Expert validation yielded a high Content Validity Index (CVI = 0.91), and field testing demonstrated a clear reduction in children’s anxiety scores post-intervention. The storytelling module is a culturally relevant, feasible, and effective pediatric nursing tool to reduce hospitalization anxiety in preschool children.